Intimate Language Variety in Animation Movie of Danshi Koukousei no Nichijou by Yasunobu Yamauchi - Pujiono, Mhd.; Taulia, Taulia; Mohamed, Noriah (Talenta Publisher, 2018)
This research elaborates language variety particularly in intimate language in Japanese animation movie Danshi Koukousei no Nichijou Episode Joshi Kousei wa Ijou High School Girls are Funky, the work of Yasunobu Yamauchi. In order to reveal the intimate language variety, Tomisaka theory was used (1997) which highlights about the change in noun and sentence within intimate language variety. The method utilized was descriptive qualitative. The result of this research is the finding of language variety such as noun and verb change and particle omission in sentences in that animation movie.